Structural behavior and environmental impact of precast ultra-high performance ductile concrete cantilever retaining walls - Nematollahi, Behzad (2012)
One of the main breakthroughs in concrete technology in the 20th century was the development of the steel fiber reinforced ultra high performance concrete (SFRUHPC), also known as steel fiber reinforced reactive powder concrete (SFR-RPC) and more commonly known as ultra high performance ‘ductile’ concrete (UHPdC) with compressive strength over 150 MPa and flexural strength over 30 MPa and remarkable improvement in durability compared to conventional concrete. Recently,due to the improved society awareness regarding the destructive effects of global warming, there is strong concern to minimize the environmental impacts (e.g. CO2 emission, embodied energy (EE)) of our structural designs. One of the solutions to achieve this goal is using the UHPdC technology which can offers considerable advantages through the efficient use of material and optimization of the structural design. Based on the revolutionary properties of UHPdC, it can offer remarkable benefits when it is utilized, as a new generation of sustainable construction material, in the fabrication of precast members for civil engineering, structural and architectural applications such as precast reinforced concrete (RC) cantilever retaining walls. On the basis of the available literature on UHPdC, no study has been carried out on the structural behavior and environmental impacts of precast UHPdC cantilever retaining walls. Further, to date there are no specific design codes/standards for analysis,design, and construction of the UHPdC structures. Therefore, this study attempted to fill this gap by evaluating the structural behavior and environmental impacts of the precast UHPdC cantilever retaining walls compared against the conventional precast RC cantilever retaining walls as benchmark of this study. In this regard, at first the geotechnical analysis of the precast UHPdC wall was carried out in accordance with Eurocode 7 (EC7): Geotechnical design- Part 1:General rules (2004) requirements. Subsequently, it was structurally designed based on the first principles (equilibrium equations) in conjunction with the Japanese Society of Civil Engineers’ Recommendations for Design and Construction of Ultra High Strength Fiber Reinforced Concrete Structures (Draft) (JSCE No.9, 2006). Afterwards, the reliability of the precast UHPdC wall was ascertained through the experimental tests with full-scale wall specimens. Four UHPdC wall specimens with the dimensions of 2.5 m in height, 2 m in length, and 2 m in width were casted. The area of the steel bars (As) used in the wall stem and the volumetric ratio of the steel fibers (Ps) used in the UHPdC composite were the test parameters. The mechanical properties of the cubes and prisms (including the cube compressive strength, flexural toughness and first cracking strength) casted from the same UHPdC composite for the wall specimens were also measured. Three wall specimens (denoted as Wall1,Wall3 and Wall4) were casted with 1.5% of steel fibers by volume of UHPdC and the test parameter was the As used in the stem which were 628 mm2 (2T20) in Wall1, 982 mm2 (2T25) in Wall3, and 1608 mm2 (2T32) in Wall4. Whilst, the other wall specimen (denoted as Wall2) was casted with 1.0% of steel fibers by volume of UHPdC. The As used in the stem of Wall2 was exactly equal to that of Wall3 (i.e.2T25) to evaluate the effect of the Ps in the UHPdC composite on the structural behavior of the wall specimen. The RC cantilever retaining wall with the dimensions of 2.5 m in height, 1 m in length, and 2.35 m in width was also analyzed with exactly the same loading, soil and ground water table conditions based on the EC7 requirements and structurally designed in accordance based on Eurocode 2 (EC2):Design of concrete structures- Part 1-1: General rules and rules for buildings (2004) to be used as the benchmark. Lastly, the environmental impact calculation (EIC) of the UHPdC wall was compared to the RC wall to prove that the UHPdC wall is a green structural member supporting the concept of sustainable development. According to the results of the experimental tests on the UHPdC wall specimens, all the specimens exhibited displacement hardening behavior after occurrence of the first crack due to inclusion of very high strength micro steel fibers bridging the cracks and limiting the crack propagation. Based on the results of Wall1, Wall3 and Wall4, the increase in the As in the wall stem led to the noticeable increase in the failure load of the specimens. Based on the results of Wall2 and Wall3, the increase in the Ps in the UHPdC composite of the wall led to the relative increase in the wall toughness causing a relative increase in the failure load of the specimen. In all of the wall specimens, the ratio of the experimental failure load to the expected failure load was on average equal to 0.66. This is due to the occurrence of the bond failure between 4T16 rebars on top of the wall heel and the UHPdC composite, resulted in the wall base failure prior to reaching the ultimate moment capacity of the wall stem (i.e. the wall stem failure). Hence it can be concluded that although based on the structural design, the area of 4T16 rebars were adequate (i.e. MEd < MRd); however, based on the experimental tests, they were not sufficient and should be increased to 4T20 or 4T25 in future wall design. Based on the EIC results with using the UHPdC wall, 86% saving in terms of material consumption, 57% saving in terms of EE, 60% saving in terms of CO2 emission, and 61% saving in terms of 100 year global warming potential (100 yr-GWP) can be achieved. Comparisons between the UHPdC wall and the conventional RC wall as the benchmark and the results of the EIC of both walls proved that the UHPdC wall is an alternative sustainable solution and a green structural member supporting the concept of sustainable development which has superior properties in all aspects compared to the conventional RC wall.